Remoteness, Urbanization, and India's Unbalanced Growth. (February 2015) - Das, Samarjit; Ghate, Chetan; Robertson, Peter E.
Highlights: We present evidence on transitional growth rates at the district level in India. We find absolute divergence and conditional convergence of growth rates. The distance to the closest urban agglomeration is a significant conditioning variable. Both policy choices and geography appear to be causing unbalanced growth. Summary: The unbalanced nature of India's growth has caused considerable concern but little is known about its causes. We use a new data set of district-level income and socio-economic data to explore the determinants of transitional growth at the district level. We find that there is absolute divergence across districts but conditional convergence once we allow for district characteristics, particularly urbanization and the distance from a major urban agglomeration. State-level effects have also significantly contributed to India's unbalanced growth. The results suggest that while geography is important, policy differences may also account for much of India's uneven growth.